Because how we talk matters: using action inquiry to nurture a coaching culture. (2nd January 2022) - Sharp, Cathy; Thomas, Joette; Brown, Ruth
ABSTRACT: This account explores the experience of an action inquiry approach to develop a coaching culture within a public service organisation. We position action inquiry as a fresh interpretation of action learning that draws on a variety of roots and traditions and focuses on the nurturing of the collective capacity to lead through everyday interactions. Working with an initial core group of staff, we expanded our reach through an iterative process to intentionally bring more people into the work. We show how we adapted our original plans to respond to the COVID pandemic, the use of stories to propel inquiry and playback insights into the inquiry process, how we deepened inquiry in some settings and how ultimately being online was an opportunity to connect people across a system that we had not anticipated. We share insights into the commissioning process and of the importance of internal sponsorship. It concludes with a striking, participant-led call to approach scaling differently by supporting the co-creation of local implementation strategies and sponsor confidence in the case to use this approach in more circumstances, where participants in action inquiry explore, rather than assume, what the organisation and its staff need.